DNA Barcode reveals mislabelling in the identification of marine fish swimming bladders for commercialization - da Silva, Caio F. [UNESP]; Daneluz, Cahique M. [UNESP]; Camacho-Oliveira, Raul B. [UNESP]; do Prado, Fernanda D. [UNESP]; Foresti, Fausto [UNESP]; Rodrigues, Carlos E.; Porto-Foresti, Fábio [UNESP] (Elsevier, 2019)
Sequences of the mitochondrial gene COI (DNA Barcode) wereused to identify marine fish swimming bladders commercialized in Brazil. The comparisons of the obtained sequences of the samples registered as catfish for the commerce with previously published data available in NCBI and BOLD showed that the fish products commercialized corresponded to two Perciform species, Pogonias cromis and Micropogonias furnieri. These results besides contradicting the formal identification of the species included in the fisheries control revealed an illegal trade of one of these species, M. furnieri that is threatened and consequently have its capture prohibited.
Keywords: Barcoding; Fisheries; Micropogonias furnieri; Pogonia cromis; Species identification